Manganese mediated oxidation of progesterone in alkaline medium: Mechanism study and quantitative determination. (20th January 2017) - Shamsipur, Mojtaba; Pashabadi, Afshin; Taherpour, Avat (Arman); Bahrami, Kiumars; Sharghi, Hashem
Graphical abstract: Highlights: This is first report on oxidation of progesterone in alkaline medium using a new manganese (III) Schiff base complex. Utilizing QM and MM, we modelled and interpreted the observed electrochemical behavior of complex on carbon and gold materials as platform. The long term stability of proposed sensor is improved relative to previously reported immunosensors for P4. A detailed mechanism was developed for the oxidation of P4. The proposed sensor was applied to quantify P4 in cow's milk. Abstract: We report here a non-immunosensing approach for the electrocatalytic oxidation of progesterone (P4) in alkaline medium using a salen-type manganese Schiff base complex (Mn(III)-SB) as a suitable electrocatalyst. We explored the role of carbon surface at glassy carbon electrode (GCE) and gold surface at glassy carbon/gold nanoparticles modified electrode (GCE/AuNPs) on immobilization of the Mn(III)-SB complex using cyclic voltammetry (CV) and density functional theory (DFT) calculations. The GCE/Mn(III)-SB displayed a pair of small redox peaks attributed to Mn(II) ⇄ Mn(III) with a small peak-to-peak separation (ΔEp ), while GCE/AuNP/Mn(III)-SB displayed redox peaks with larger densities, but with a wider ΔEp . A combined molecular mechanics (MM) and quantum mechanics (QM) study were carried out to investigate the variation of surface configuration and energy barrier, when the Mn(III)-SB immobilization was modeled on GCE and GCE/Au surface. Cyclic voltammetry and hydrodynamic amperometry were used for the quantitative determination of P4. A limit of detection (LOD) of 11.4 nM was obtained using amperometry. The sensor retained 91% of its original response after 3 months, which is improved compared to previously reported P4 immunosensors. For the first time, a detailed mechanism for oxidation of P4 in alkaline medium was suggested. The proposed sensor was utilized to determine progesterone in milk samples.